Strategi Pembelajaran Group Resume Keefetifannya Terhadap Motivasi Belajar Siswa Di SMP - qurota a'yun a'yun (EDU-BIO: Jurnal Pendidikan Biologi, 2018)
This research discusses the application of Stratgi Group Resume learning to students' learning motivation at Betara High School 1 in Tanjung Jabung Barat. This research is a quantitative research using Quasi Experiment method with One Group Pretest-posttest Design, data collection is done with motivation questionnaire and student activity observation sheet. The sample in this study were students of class XI IPA 1 taken by cluster random sampling. Judging from the results of the test "t" shows the difference in learning motivation at Pretest and Posttest. This is evidenced by the results of the T test which obtained a value of 2.01 <3.866> 2.67 at a significance level of 5% and 1%. From the results of the Phi correlation test which obtained a value of 0.273 <0.57> 0.354 at a significance level of 5% and 1%. That is, based on the calculation of the T test and the correlation of phi, the alternative hypothesis is accepted and the hyposis is rejected. It can be concluded that there is an effect of the application of Group Resume learning strategies on students' learning motivation in class XI Science 1 at State Senior High School 1 Betara Tanjung Jabung Barat. Keywords : Resume group learning strategy, Learning Motivation.